2019
DOI: 10.3390/su12010228
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude of Tourist Destination Residents towards the Effects of Overtourism—Kraków Case Study

Abstract: Scientific research into the effect of tourist traffic in a tourist area have shown that the excessive concentration of tourist traffic leads to overcrowding in attractive locations, over-advertising, and aggressive commercialization, which lower the aesthetic quality of tourists’ experiences and result in the degradation of natural and cultural resources. The effect of excessive tourist numbers is an increase in the price of services, rental fees, and real estate. In historical cities, it causes the gentrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 40 publications
(47 reference statements)
1
64
0
8
Order By: Relevance
“…Intermittently meeting with tourists could affect the character formation of residents according to the longitudinal question. The residents' positions on tourists are subjective and difficult to measure [22], and a valid theory is needed to better understand the perceptions of tourists [63]. This study, prior to using a theoretical approach, observed, understood, and expanded the foundation of the views of the relationships that are formed among residents.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Intermittently meeting with tourists could affect the character formation of residents according to the longitudinal question. The residents' positions on tourists are subjective and difficult to measure [22], and a valid theory is needed to better understand the perceptions of tourists [63]. This study, prior to using a theoretical approach, observed, understood, and expanded the foundation of the views of the relationships that are formed among residents.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, with repeated and intermittent encounters with various targets, residents become accustomed to their relationship with tourists. A large number of tourists visiting an area strengthens the pride of the residents because it means that their destination is superior [22]. Thus, due to the interest of tourists, residents may preserve the valuable natural environment and traditional culture in the destination [21].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitude towards overtourism among Wrocław inhabitants who are not directly involved in tourism and people who do not draw income from this economic sector has not been covered in this study and remains a problem for further research. The attitudes of residents and tourist business community representatives towards excessive concentration of tourist traffic have been interestingly depicted by Szromek et al [55] and Kowalczyk-Anioł and Zmyślony [56] in the example of Krakow agglomeration. Analyses of opinions of various types of tourist traffic stakeholders towards the phenomenon of overtourism (including those pointing to a conflict of interests among tourist stakeholders) were also conducted in relation to other Polish cities of high tourist attractiveness, among others, Zakopane and Kazimierz Dolny [57].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is necessary to emphasize the creation of modern and well-designed public spaces (expansion of tourism beyond the city centre), which would improve the quality of the tourist offer and would effectively address the dangers of excessive concentration of tourist traffic and gentrification phenomena in the city centre. Szromek et al [55] postulate tourist traffic management that would allow for quick and effective responses to changes, by implementing the concept of agile tourism, defined as adjusting organizational culture and quickly responding to market changes [61]. 7.…”
mentioning
confidence: 99%